Erdődy Gábor (főszerk.); Cúthné Gyóni Eszter, Wirthné Diera Bernadett (szerk.): Visszatekintés a 19–20. századra. Tanulmányok - Somodi, Imre (Acta Scientiarum Socialium, 2012)
Gábor Erdődy (editor-in-chief); Eszter Gyóni Cúthné, Bernadett Diera Wirthné (eds.): Retrospection of the 19th and 20th Century. Studies. Loránd Eötvös University Doctoral School of Historical Sciences Doctoral Program of Modern Hungarian History, Budapest, 2011, 263 pp. This volume contains the selected studies of the PhD students of Loránd Eötvös University Doctoral School of Historical Sciencies Doctoral Program of Modern Hungarian History. These papers focus on the political history of Hungary in the period of the Austro-Hungarian Monarchy, the political and military occurences of the Horthy-era, and the contradictions of the socialist era.